Native English speakers' authority in English: Do Chinese speakers of English care about native English speakers' judgments?. Issue 1 (21st December 2015) - Wang, Ying
Abstract : Given the unprecedented spread of English, native English speakers (NESs) have been estimated to number 508 million by 2050 (Graddol, 1997: 27), while a bold estimation of speakers of English is 2 billion by 2050 (Crystal, 2008: 4–5). The international demographic profile of English presents a scenario whereby the development of English depends on how this language is used by non-native English speakers (NNESs), who are obviously in the majority for English use (e.g. Brumfit, 2001: 116; Crystal, 2008: 6; Graddol, 1997: 10; Mauranen, 2012; Seidlhofer, 2011: 7–8). While the importance of the number of English speakers globally is acknowledged, English in China remains a particularly interesting area for linguists. Not only English is widely learned in China, but also Chinese speakers of English are increasingly involved in intercultural encounters. In Graddol's (1997, 2006) discussion of the future of English, a comprehensive account is put forward about China, a country that has statistical significance for the development of English, given its large population of people who know English and its economic development. As Crystal (2008: 5) notes:[I]f India is the significant factor in relation to second-language speakers (in the sense of countries where English has some sort of special status), then China is surely the corresponding factor in relation to foreign-language speakers (in the sense of countries where the language has no official status). In this sense, it would seem that China will play an important role in shaping the profile of English use in the future. If this is an acceptable hypothesis, the development of English in China has implications for the future world of English use.